Developing open source materials for foundation phase: Diverse spaces for collaboration - Moodley, D.; Smith, C.G.A.; Joubert, I.; Singh, P.; Sookraj, R.; Zama, Z. (South African Journal of Higher Education, 2016)
Determining a space for collaborative activities involves the creation of a unique space which encourages reciprocal learning and the creation of products that can benefit all participants. The aim of this article was to explore the experiences of group members in this collaborative space. The group consisted of lecturers from different Higher Education Institutions (HEIs) tasked to create quality open-source materials for teaching and learning Literacy in Foundation Phase at HEIs (coming together and work in one space) in the endeavour to connect and share collaboratively. Selected components of the theories of space suggested by Lefebvre and Soja were employed to explain the data which were gleaned through interviews with all participants in the group. This paper makes two important contributions: firstly, it substantively presents a deeper understanding of the experiences of the group in collaborative work and secondly, through the use of a theoretical framework on space, offers insights into the nature of collaboration within diverse spaces.